Aetiology and trends of rates of stillbirth in a tertiary care hospital in the north of India over 10 years: a retrospective study. (13th August 2019) - Sharma, B; Prasad, GRV; Aggarwal, N; Siwatch, S; Suri, V; Kakkar, N
Abstract : Objective: To analyse the aetiology of stillbirth and its changing trends in a single tertiary care referral institute of northern India over a 10‐year period (2007–2016). Design: Retrospective study. Setting: Tertiary care hospital in the north of India. Sample: Medical records of all mothers who delivered a stillborn at the institute. Methods: Data was collected from monthly and annual perinatal audits and causes of stillbirths were classified using Simplified CODAC classification. Annual reduction rate was calculated by linear regression analysis and Cusick test for the changing trends over 9 years. Main outcome measures: Of 54 160 births, 3678 babies were stillborn. Over 9 years, the annual stillbirth rate has reduced significantly from 73.6 to 62.0 per 1000 total births with an average annual reduction rate of 1%. The most common causes of stillbirths were hypertensive disorders of pregnancy (27.6%), antepartum haemorrhage (19.5%), and congenital anomalies (9.3%). Conclusion: The annual reduction rate (1%) of stillbirth remains low. The aetiology of stillbirths remains unchanged over a 10‐year period and hypertensive disorder of pregnancy remains the single most preventable cause of stillbirth. Tweetable abstract: Analysis of stillbirths over a 10‐year period in an Indian institute showed a high but declining trend with annual reduction rate of 1%. Tweetable abstract: Analysis of stillbirths over a 10‐year period in an Indian institute showed a high but declining trend with annual reduction rate of 1%.